Konstruksi Primer Untuk Mendeteksi Mutasi Gen rpoB Mycobacterium tuberculosis Dengan Metode Amplification Refractory Mutation System (ARMS)-PCR - Arif Sardi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
Quickly recognize drug resistance in Mycobacterium tuberculosis is very important for the efficiency of the treatment and control of the disease. More than 95% of RIF resistance occurs due to point mutations in the 81-bp region of the rpoB gene M. tuberculosis. Generally, the mutation occurs at codon 531, 526 and 516. One of method to detect the mutation is using ARMS-PCR. In order to apply the ARMS-PCR technique to detection of mutations needed a special and specific primer. Primer design process using computer software